Phase diagram of the iron arsenide superconductors Ca(Fe1-xCox)2As2(0 [bigger than or equal] x [less than or equal] 0.2) - Harnagea, Luminita; Singh, S.; Friemel, G.; Leps, N.; Bombor, D.; Abdel-Hafiez, M.; Wolter, A. U. B.; Hess, C.; Klingeler, Rüdiger; Behr, G.; Wurmehl, S.; Büchner, B. (Physical review. B, Condensed matter and materials physics, 2011)
Plateletlike single crystals of the Ca(Fe1−xCox )2As2 series having lateral dimensions up to 15 mm and thicknesses up to 0.5 mm were obtained from the high-temperature solution-growth technique using Sn flux. Upon Co doping, the c axis of the tetragonal unit cell decreases, while the a axis shows a less significant variation.
Im Titel ist [bigger than or equal] und [less than or equal] als mathematisches Zeichen dargestellt
Im Titel "1-x" bei "Fe" und "x" bei "Co" tiefgestellt
Im Titel ist "2" hinter der Klammer von "(Fe1-xCox)" und bei "As" tiefgestellt
Gesehen am 03.08.2022